Psychoanalysis in the Novel Garis Luka by Khairani Hasan - Suryani, Ifa; Rahayu, Sri (Al-Lisan: Jurnal Bahasa, 2025)
Background: A character's personality shapes a compelling and high-quality novel. It not only drives the storyline and deep insights into human nature, emotions, and experiences, allowing readers to connect with the narrative on a profound level. Aims: This research examines the significance of the characters' personality traits in Khairani Hasan's novel "Garis Luka." Methods: This study is qualitative and descriptive. Hermeneutic techniques were employed to gather data, which was subsequently analyzed using Sigmund Freud's theories on character personalities (1901). Results: The research findings indicated that the aspects of a character's personality associated with the id (pleasure principle), ego (the conscious part of the personality that mediates between the id and reality), and superego played a significant role in novels. In this novel, the elements of the character's personality are well depicted, with 115 data points identified from the research. The character's personality was tied to the id in 61 instances, the ego in 36 instances, and the superego in 18 instances. Implications: This research can serve as a resource for developing more varied, creative, and innovative literary learning materials and enhance knowledge about novel psychoanalysis.